High‐Frequency Spinal Cord Stimulation at 10 kHz for the Treatment of Complex Regional Pain Syndrome: A Case Series of Patients With or Without Previous Spinal Cord Stimulator Implantation. Issue 3 (7th January 2019) - Gill, Jatinder S.; Asgerally, Abbas; Simopoulos, Thomas T.
Abstract: Background: High‐frequency spinal cord stimulation at 10 kHz (HF10‐SCS) has been demonstrated to provide enhanced and durable pain relief in patients with chronic back and radiating leg pain. Patients with pain related to complex regional pain syndrome (CRPS) in the chronic stages are commonly challenging to treat and often receive traditional spinal cord stimulation (SCS). Very little information is currently available about the therapeutic outcomes following application of high‐frequency stimulation in this cohort of patients. Methods: The purpose of the retrospective case series was to report on the initial experience of HF10‐SCS in 13 patients with CRPS, some of whom had been exposed to low‐frequency SCS. A temporary trial of HF10‐SCS was carried out for 1 week, and those achieving a minimum of 50% pain intensity reduction underwent implantation. Successful responders were those who achieved a 50% decrease in pain intensity on subsequent follow‐up. Results: Thirteen patients were trialed, 12 of whom went on to receive a permanent implant. Of the patients receiving permanent implants, the responder rate (50% pain relief) was 67% (95% confidence interval [CI] 0.34 to 0.90), with an average follow‐up period of 12.1 ± 4.6 months. Of the 5 patients who had sympathetically independent pain, 3 were responders, and of the 7 patients who had sympathetically mediated pain, 5 were responders. There were no adverse events. Conclusion: This small case series suggests that HF10‐SCS may be a viable option for patients with CRPS who have chronic intractable pain, including those who had suboptimal results from traditional SCS.